2013
DOI: 10.1080/15381501.2012.749820
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Trauma on Recent Inconsistent Condom Use Among Young Black Gay and Bisexual Men

Abstract: The authors examined lifetime prevalence of sexual assault, emotional abuse, and physical violence, in a statewide sample of 180 Black gay and bisexual males ages 14 to 24. Rates of exposure to each form of abuse was high; 33% reported sexual assault, 74% reported at least one type of physical violence, and 91% reported at least one type of emotional abuse. Co-occurring trauma was the dominant pattern. Sexual assault and number of types of trauma experienced were associated with inconsistent condom use. Physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 50 publications
1
14
1
Order By: Relevance
“…On the basis of previous analyses (Miller, Mcnall, Reed, & Forney, 2013), we anticipated that participants from the Detroit area would exhibit different health profiles than participants from elsewhere. Of the 29 nonsyndemic young men, 97% were residents of the Detroit Metropolitan Area.…”
Section: Sexual Behaviormentioning
confidence: 99%
“…On the basis of previous analyses (Miller, Mcnall, Reed, & Forney, 2013), we anticipated that participants from the Detroit area would exhibit different health profiles than participants from elsewhere. Of the 29 nonsyndemic young men, 97% were residents of the Detroit Metropolitan Area.…”
Section: Sexual Behaviormentioning
confidence: 99%
“…These relationship features can discourage condom use through beliefs that condoms reflect a lack of trust in one’s partner, or the assumption that sex with a primary partner is safe (Kubicek et al, 2008). Moreover, an emerging line of research links elevated HIV risk in YMSM with problematic relationship characteristics, including feeling trapped (Mustanski et al, 2011) and experiencing intimate partner violence (IPV) (Miller, Reed, McNall, & Forney, 2013). These negative relational factors impact YMSM’s perceived ability or motivation to adopt or advocate for safer sex behaviors with one’s partner.…”
Section: Relationship Characteristics and The Relo-imb Modelmentioning
confidence: 99%
“…Identifying the key predictors of condom use and condom decision making is of vital importance in addressing the burgeoning HIV epidemic among AGBM. Several studies of AGBM have found that an increase in HIV risk behaviors, including reduced condom use, are associated with factors including relationship length, 5,6 illicit drug use 7 , sexual partner age 8 , and experiences of trauma 9 (for a review see 1 ). Additionally, engagement in unprotected anal intercourse (UAI) has been shown to be significantly associated with individual differences in impulsive decision making and sensation-seeking 10 .…”
Section: Introductionmentioning
confidence: 99%